2013
DOI: 10.1093/sf/sot099
|View full text |Cite
|
Sign up to set email alerts
|

Unequal Trajectories: Racial and Class Differences in Residential Exposure to Industrial Hazard

Abstract: The unequal exposure to industrial hazards via differential residential attainment and/or differential sitings of toxic facilities is a long-standing environmental justice issue. This study examines individual trajectories of residential exposure to the risk of industrial hazard over nearly two decades. Using a latent class growth analysis on longitudinal geocoded data merged with the neighborhood-level pollution measures, we discover large racial differences in trajectories of pollution exposure. A majority o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 47 publications
5
74
0
Order By: Relevance
“…A fuller examination of the direct and indirect mechanisms through which air pollution operates on psychological health, however, was beyond the scope of the present study. Future research in this area would benefit from explicit assessments of the more proximal determinants linking air pollution and psychological distress, including various physiological and (mal)adaptive behavioral responses to environmental hazards, especially among racial/ethnic minority groups and other vulnerable populations who are disproportionately exposed to air pollution 56,57 .…”
Section: Discussionmentioning
confidence: 99%
“…A fuller examination of the direct and indirect mechanisms through which air pollution operates on psychological health, however, was beyond the scope of the present study. Future research in this area would benefit from explicit assessments of the more proximal determinants linking air pollution and psychological distress, including various physiological and (mal)adaptive behavioral responses to environmental hazards, especially among racial/ethnic minority groups and other vulnerable populations who are disproportionately exposed to air pollution 56,57 .…”
Section: Discussionmentioning
confidence: 99%
“…10 Black Americans, including those in middle and upper classes, are more likely to live in poorer-quality and more economically disadvantaged neighborhoods than White Americans of the same economic class. [18][19][20][21][22] As a result, large numbers of Blacks are exposed to the deleterious conditions associated with disadvantaged neighborhoods. 23,24 However, longitudinal data on neighborhood SES and mortality among Black Americans are limited.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent national study combining individual-level mobility data with neighborhood-level industrial hazard risks, Crowder and Downey [41] found that "black and Latino householders move into neighbourhoods with significantly higher hazard levels than do comparable whites". Conversely, in another national study [42] of residential mobility between 1991 and 2007, the odds of starting with low pollution exposure but ending with high levels of exposure was 38 percent higher for immobile black households than for immobile whites. Likewise, a longitudinal analysis of Los Angeles' riskscape of hazardous waste Transport, Storage, and Disposal Facilities (TSDFs) found that when "controlling for other factors, minorities attract TSDFs but TSDFs do not generally attract minorities" [43].…”
Section: Environmental Inequities and Gentrificationmentioning
confidence: 84%